Ions channels/transporters and chloroplast regulation. Issue 1 (1st July 2015) - Finazzi, Giovanni; Petroutsos, Dimitris; Tomizioli, Martino; Flori, Serena; Sautron, Emeline; Villanova, Valeria; Rolland, Norbert; Seigneurin-Berny, Daphné
Graphical abstract